Is health a just transition issue? cross-cutting multiple crisis: Economic, unemployment, climate and healthcare - Camargo, J. (Sustainable policies and practices in energy, environment and health research: Addressing cross-cutting issues, 2022)
In the aftermath of the Covid-19 pandemia, economic crisis is upon society. Unemployment and layoffs coincide with the need for a revolutionary shift in energy systems and the whole productive system. The push for economic recovery designed in most countries does include a response to climate science, though not at the level required (national and regional plans currently have targets that are not in line with keeping temperatures increase under 1.5 ℃ by 2100). Climate Jobs campaigns in different countries have pushed for the creation of political agendas to shift countries’ towards a 45–50% global cut in emissions by 2030, in a framework called “Just Transition”. This framework has been connecting labour and climate, but the focus has been kept mostly out of health issues and the strenuously tested health systems and healthcare workforce, which are a key component of the “care economy”, a central demand of Climate Justice. From the health issues prevalence in labour (in fossil fuel workers in particular) to the increase in health problems connected to the already inevitable impacts of climate change, can Health and healthcare workers become central in the discussion of a new productive system and can healthcare jobs be part of these campaigns and political programs for Just Transition?